Variation of Nordic classic ski characteristics from Norwegian national team athletes - Breitschädel, F. (Procedia Engineering, 2012)
In cross country skiing the technical equipment of an athlete constitutes a substantial part of the total performance. Thus, the focus of this study was (1) to determine if different Norwegian national athletes select Classic skis with similar characteristics and (2) to describe the key parameters for the two ski categories (warm and cold). Classic cross country skis (205 pairs) from the Norwegian men's and women's national ski teams were tested under lab conditions. Clear differences between various factors (camber height at the balance point, stiffness, length of contact zone and opening characteristics) were found. Lower camber height for cold skis and higher ones for warm skis can be explained by the wax routines and their necessities. The nominal contact zones for both men's and women's skis from the warm category are shorter than corresponding contact zones from skis of the cold category.